An audit of inter‐hospital transfers of children with abdominal pain and their associated medical imaging findings. Issue 1 (27th October 2021) - Reddan, Tristan; Halligan, Toni; Corness, Jonathan
Abstract: Introduction: Ultrasound is a common first‐line examination in acute abdominal pain in children. In rural and regional areas, ultrasound is an important factor in decisions to transfer paediatric patients for tertiary care. Transfers can be over a considerable distance, by road and air, and at great cost. This audit reviewed ultrasound findings in children transferred to an Australian paediatric hospital for acute abdominal pain. Methods: Children transferred for acute abdominal pain between July 2018 and June 2019 was identified. Imaging findings at the transferring and receiving facility were reviewed, along with the patient's electronic medical record. Suspected and final diagnoses were recorded, and the accuracy of imaging evaluated. Results: There were 172 transfers identified, mean age was 6 years 1 month, 66.3% were boys. Mean transfer distance was 55.4 km. The majority were suspected acute appendicitis (63.9%), followed by intussusception (20.3%), and hypertrophic pyloric stenosis (14.5%). The majority of suspected diagnoses were ultimately false positives including pyloric stenosis, 52.0%; appendicitis, 50.9% and ileo‐colic intussusception, 74.3% of cases negative. Conclusion: Improved diagnostic accuracy in evaluating causes of acute paediatric abdominal pain with ultrasound, particularly appendicitis, pyloric stenosis, and intussusception is required. Targeted education and clinical support mechanisms may reduce potentially unnecessary inter‐hospital transfers and their considerable associated costs.